The effect of staged TIP urethroplasty on proximal hypospadias with severe chordee - Xie, Qike; Liu, Yuling; Zhao, Xiangyou; Huang, Junqiang; Chen, Chao (Frontiers in Surgery, 2022)
Background: Proximal hypospadias with severe chordee is still a formidable challenge for most pediatric urologists, but the approach remains controversial. We described a modified 2-stage technique to repair proximal hypospadias with severe chordee. Methods: We retrospectivly identified 53 children referred for proximal hypospadias with severe chordee from July 2016 to July 2019 that underwent 2-staged urethroplasty. In group 1, the children were repaired with staged TIP urethroplasty, while Byars 2-stage urethroplasty in group 2. We corrected chordee by releasing all remaining attachments to the corpora after degloving the penis, transceting the urethral plate and dorsal plication. The mean age of patients in the first stage of surgery was 26.6 months in group 1 and 24.8 months in group 2. Postoperative complications in the two groups included: fistula, urethral stricture, urethral diverticulum, glanular dehiscence. Results: 20 cases were repaired with staged TIP urethroplasty(group 1), and 33 cases were repaired with Byars 2-stage urethroplasty(group 2). The length of follow-up in group 1 was 39.8±10.1 months, which 38.1±8.7 months in group 2(P＞0.05). After the second stage of surgery, 1 cases (5%) in group 1 and 11 cases (33.3%) in group 2 developed urinary fistula (P＜0.05). 1 case (5%) in group 1 and 3 cases (9.1%) in group 2 had urethral stricture (P＞0.05). All strictures were cured by repeated dilation and no patient required reoperation. No cases in group 1 and 1 case(3%) in group 2 had urethral diverticulum (P>0.05). There were no residual chordee in both groups. 2 cases (10%) in group 1 and 13 cases (39.3%) in group 2 required reoperation (P＜0.05). Conclusions: Staged urethroplasty is appropriate to repair proximal hypospadias with severe chordee. Particularly, staged TIP urethroplasty is a good choice for the patients with proximal hypospadias and severe chordee, especially the patients with better penile development, wider urethral plate, larger glans, and deeper navicular fossa of urethra.